Pengungkapan Diri Gen Z dalam “Komunitas Marah Marah” di Twitter - Noviana Safira; Sumardjijati Sumardjijati (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study examines the practice of self disclosure, which is the disclosure of personal information to others, carried out by Generation Z through komunitas marah marah on Twitter. The background of this study is formed by the increasing emotional openness and intense use of language. The objective of the study is to understand the forms of self disclosure that emerge and the factors influencing them, such as personality, gender, post topics, media anonymity, and social environment. This study employs a descriptive qualitative approach, using in-depth interviews and documentation of informants' posts. The results show that komunitas marah marah serve as an alternative space for Gen Z to anonymously express personal experiences and emotions. Social media anonymity provides a sense of safety when expressing sensitive topics, especially for introverted individuals. The lack of support in the real world also drives them to seek validation, empathy, and solutions through online communities. Thus, komunitas marah marah function as safe spaces that allow Gen Z to express themselves more freely, free from the pressure of social norms.